If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -1(-6) = 12 Multiply -1 * -6 a + 6 = 12 Reorder the terms: 6 + a = 12 Solving 6 + a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + a = 12 + -6 Combine like terms: 6 + -6 = 0 0 + a = 12 + -6 a = 12 + -6 Combine like terms: 12 + -6 = 6 a = 6 Simplifying a = 6
| -12*(-55)*0= | | 8x+7=90 | | 5-x=(1/2x)+4 | | 4z+3z-6-7z=6 | | 7x=2x+1 | | -31+(-28)-(-14)-16= | | 8f-4=6f+26 | | 3y/x | | 3a+4b=(1-2c)/d | | (x/3)-4=5 | | 1/5x=10-5 | | 5(3+x)+1=71 | | 175.000+550.00-1.00x=220.650 | | -5+6x+4x^2+x^3=0 | | 3z+6=17 | | 0.5x+11=17 | | 9(x-5)=x+22(1/2) | | k/5+5=7 | | (-3/5)x=15 | | x-27=19 | | 4x^2+x^3=0 | | 4p^2-11p-3=0 | | 6x+4x^2=0 | | 0.5=2(0.7)x+x^2 | | -1/2(5) | | 8x^5-64x^3=0 | | 7x+5y+10=0 | | x+13 | | 4*4-2=y+4 | | (2s)+(7s-18)=90 | | 9x+27=(9x+2)+9 | | x^3+4x^2+6x-5=0 |